Multiple Precursor Proteins of Thanatin Isoforms, an Antimicrobial Peptide Associated With the Gut Symbiont of Riptortus pedestris - Lee, Junbeom; Cha, Wook Hyun; Lee, Dae-Weon (Frontiers in Microbiology, 2022)
Thanatin is an antimicrobial peptide (AMP) generated by insects for defense against bacterial infections. In the present study, we performed cDNA cloning of thanatin and found the presence of multiple precursor proteins from the bean bug, Riptortus pedestris. The cDNA sequences encoded 38 precursor proteins, generating 13 thanatin isoforms. In the phylogenetic analysis, thanatin isoforms were categorized into two groups based on the presence of the membrane attack complex/perforin (MACPF) domain. In insect-bacterium symbiosis, specific substances are produced by the immune system of host insect and are known to regulate the population of symbionts. Therefore, to determine the biological function of thanatin isoforms in symbiosis, the expression levels of three AMP genes were compared between aposymbiotic insects and symbiotic R. pedestris. The expression levels of the thanatin genes were significantly increased in the M4 crypt, a symbiotic organ, of symbiotic insects upon systemic bacterial injection. Further, synthetic thanatin isoforms exhibited antibacterial activity against gut-colonized Burkholderia symbionts rather than in vitro-cultured Burkholderia cells. Interestingly, the suppression of thanatin genes significantly increased the population of Burkholderia gut symbionts in the M4 crypt under systemic Escherichia coli K12 injection. Overgrown Burkholderia gut symbionts were observed in the hemolymph of host insects and exhibited insecticidal activity. Taken together, these results suggest that thanatin of R. pedestris is a host-derived symbiotic factor and an antimicrobial peptide that controls the population of gut-colonized Burkholderia symbionts.